(3GdNUGFU (B/s - (3GHf Lfj, YKeGf Hf Lfj GdehUdj,s (3J(B. 392 (3g`s; (3TQjOI,GdTQHjfjs ((3GdbGgQI (B:s (3OGQ GdMOjK,s, 2007)
(3jJfGhd GdNUGFU GddZhjI GdYQHjI GddZhjI dGHf Lfj hjSJYQV GdaUd Hjf GdcdGe hGdbhd hGddZI heG gj hGdfMh hGdEYQGH hZjQgG ef GdCHhGH GdeJfhYI(B.s
Keywords: (3GddZI GdYQHjIs -- (3fMhs